1981
DOI: 10.1177/002224378101800202
|View full text |Cite
|
Sign up to set email alerts
|

On the Prediction Power of Market Share Attraction Models

Abstract: Logical consistency of market share models has received considerable attention in the recent marketing literature. The reports suggest that, at least theoretically, attraction-type specifications are more easily justified than the ones commonly used in empirical work. The authors examine whether the theoretical superiority also implies a better predictive performance. The empirical results give a tentatively affirmative answer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The basic justification for some of these specifications is rooted in what has been known as Kotler's fundamental theorem (on market share) and the axiomatic approach in the Bell-Keeney-Little market share theorem (Bell, Keeney, and Little 1975). Since the MCI and the MNL models imply immediately that each brand's market share is nonnegative and the sum of market shares of all brands is unity, both specifications satisfy the so-called logical-consistency requirements (Naert and Bultez 1973). While these two models have not always resulted in superior performance in terms of predictive accuracy in comparison to the other models, it has been argued that they nevertheless yield more meaningful interpretations regarding market-share elasticities and sales-volumes elasticities, notions which managers may find most useful.…”
Section: Introductionmentioning
confidence: 99%
“…The basic justification for some of these specifications is rooted in what has been known as Kotler's fundamental theorem (on market share) and the axiomatic approach in the Bell-Keeney-Little market share theorem (Bell, Keeney, and Little 1975). Since the MCI and the MNL models imply immediately that each brand's market share is nonnegative and the sum of market shares of all brands is unity, both specifications satisfy the so-called logical-consistency requirements (Naert and Bultez 1973). While these two models have not always resulted in superior performance in terms of predictive accuracy in comparison to the other models, it has been argued that they nevertheless yield more meaningful interpretations regarding market-share elasticities and sales-volumes elasticities, notions which managers may find most useful.…”
Section: Introductionmentioning
confidence: 99%
“…The few exceptions are the recent comparison of models by Naert and Weverbergh (1981) and two earlier studies by Weiss (1969) and Rao (1972). As Naert and Weverbergh note, however, only tentative answers to questions about the relative performance of different models are available and further empirical work addressing this important issue is necessary.…”
Section: Some Intermediate Level Of Parameterization Be Used?mentioning
confidence: 98%
“…Though models with brand-specific response parameters are most meaningful for decision makers, Naert and Weverbergh (1981) have found that constraining the parameter values improves the predictive performance of market share models.…”
Section: Some Intermediate Level Of Parameterization Be Used?mentioning
confidence: 99%
“…We choose to analyze market shares and to measure the effectiveness of marketing instruments of different brands using the familiar market share attraction model (Bronnenberg, Mahajan, & Vanhonacker, 2000;Cooper & Nakanishi, 1988;Leeflang & Reuyl, 1984;Naert & Weverbergh, 1981). An advantage of using market shares is that these are in general not influenced by category expansion or contraction.…”
Section: Attraction Modelmentioning
confidence: 99%